Teaching vocabulary in all classrooms - Blachowicz, Camille L. Z. (Allyn & Bacon, 2010)
"Expanded coverage of metacognitive strategies for learning vocabulary using contextual cues and references [as well as] ideas for dealing with student diversity, with an increased focus on struggling readers, English language learners, and older students." --Back cover.